Computational prediction of the aerodynamic performance of JAXA standard high lift configuration model (2017)
Computational fluid dynamics and computer aided simulations are becoming increasingly more important for aerodynamics and aeronautics, since they can complement experimentation up to certain extent. However, CFD results are not 100% accurate since when compared with real experimental data they usually have a certain grade of error, as they utilize simplified models with significant assumptions and simplifications. Taking this into account, the need for more accurate simulations becomes increasingly important in order to reduce experimentation costs and develop proper models specific for each kind of simulation. In this dissertation project a CFD simulation about a civil aircraft model was developed, using two different turbulence models, Spallart Almaras and {kappa}-{omega} SST. The aircraft model used corresponds to JAXA Standardized Model (JSM) which is part to one of the test cases of NASA&AIAA 3rd High Lift Prediction Workshop. The main purpose of this test case of the workshop is to compare the results obtained via computer simulation with the results previously obtained experimentally in a wind tunnel. Although the obtained lift and drag coefficients were comparable to experimental data, proper simulation convergence was not reached. It is believed as a hypothesis that the cause of the problem is that the used meshes were not suitable for the simulation and solver used